Robust Transceiver Design for SWIPT DF MIMO Relay Systems With Time-Switching Protocol - Lee, J.B.; Rong, Yue; Gopal, Lenin; Chiong, Choo W.R. (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2021)
In this article, we investigate a dual-hop simultaneous wireless information and power transfer decode-and-forward multiple-input and multiple-output relay communication system, in which the relay node harvests energy based on the radio frequency (RF) signal transmitted from the source node through the time-switching (TS) protocol to decode and forward the re-encoded information to the destination node. With the consideration of the channel estimation error, the joint optimization of the TS factor and source and relay precoding matrices is proposed with robustness against the channel state information mismatch to maximize the mutual information (MI) between the source and destination nodes. We derive the optimal structure of the source and relay precoding matrices to simplify the transceiver optimization problem under fixed and flexible power constraints. Numerical examples demonstrate that the proposed algorithms with robustness provide better MI performance compared to the nonrobust algorithm.